Nicotine-induced Genetic and Epigenetic Modifications in Primary Human Amniotic Fluid Stem Cells - Upadhyaya, Prabin; Milillo, Cristina; Bruno, Annalisa; Anaclerio, Federico; Buccolini, Carlotta; Dell'Elice, Anastasia; Angilletta, Ilaria; Gatta, Marco; Ballerini, Patrizia; Antonucci, Ivana (Current Pharmaceutical Design, 2024)
Background: Smoking during pregnancy has been linked to adverse health outcomes in offspring, but the underlying mechanisms are not fully understood. To date, the effect of maternal smoking has been tested in primary tissues and animal models, but the scarcity of human tissues limits experimental studies. Evidence regarding smoking-related molecular alteration and gene expression profiles in stem cells is still lacking. Methods: We developed a cell culture model of human amniotic fluid stem cells (hAFSCs) of nicotine (NIC) exposure to examine the impact of maternal smoking on epigenetic alterations of the fetus. Results: NIC 0.1 μM (equivalent to “light” smoking, i.e., 5 cigarettes/day) did not significantly affect cell viability; however, significant alterations in DNA methylation and N6-methyladenosine (m6A) RNA methylation in hAFSCs occurred. These epigenetic changes may influence the gene expression and function of hAFSCs. Furthermore, NIC exposure caused time-dependent alterations of the expression of pluripotency genes and cell surface markers, suggesting enhanced cell stemness and impaired differentiation potential. Furthermore, NICtreated cells showed reduced mRNA levels of key adipogenic markers and hypomethylation of the promoter region of the imprinted gene H19 during adipogenic differentiation, potentially suppressing adipo/lipogenesis. Differential expression of 16 miRNAs, with predicted target genes involved in various metabolic pathways and linked to pathological conditions, including cognitive delay and fetal growth retardation, has been detected. Conclusion: Our findings highlight multi-level effects of NIC on hAFSCs, including epigenetic modifications, altered gene expression, and impaired cellular differentiation, which may contribute to long-term consequences of smoking in pregnancy and its potential impact on offspring health and development.
Keywords: mRNAs